2016
DOI: 10.1177/0004563216633489
|View full text |Cite
|
Sign up to set email alerts
|

Clinical relevance of trace element measurement in patients on initiation of parenteral nutrition

Abstract: Background and Aims Serum zinc, copper and selenium are measured in patients prior to commencing on parenteral nutrition; however, their interpretation can be difficult due to acute phase reactions. We assessed (i) the relationship of raised C-reactive protein with trace elements and albumin (ii) benefits of measuring trace elements when C-reactive protein is raised in patients requiring short-term parenteral nutrition. Methods Samples were collected for zinc, copper, selenium and albumin at baseline and then … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 26 publications
(35 reference statements)
0
5
0
Order By: Relevance
“…Low blood levels therefore do not necessarily indicate deficiency or even depletion. Within 24 h of elective surgery in otherwise healthy individuals, plasma concentrations of many trace elements and vitamins have fallen markedly, without any change in whole body MN status [38]. The effects of inflammation in response to acute trauma or infection is usually rapid but may also be prolonged in chronic illness.…”
Section: Impact Of Inflammationmentioning
confidence: 99%
See 1 more Smart Citation
“…Low blood levels therefore do not necessarily indicate deficiency or even depletion. Within 24 h of elective surgery in otherwise healthy individuals, plasma concentrations of many trace elements and vitamins have fallen markedly, without any change in whole body MN status [38]. The effects of inflammation in response to acute trauma or infection is usually rapid but may also be prolonged in chronic illness.…”
Section: Impact Of Inflammationmentioning
confidence: 99%
“…Albumin is a carrier protein for many MNs including zinc. Its level may be influenced by dilution, and by inflammation, being a negative acute phase protein [38]. Therefore, albumin determination is desirable whenever a series of MNs is determined.…”
Section: Recommendationmentioning
confidence: 99%
“…Additionally, as ceruloplasmin is an acute phase reactant, ceruloplasmin and copper levels can be elevated in inflammatory states even in the setting of marginal copper deficiency [7]. In a recent study of 166 patients, copper levels had no correlation with C-reactive protein (CRP) levels, unlike zinc, selenium, and albumin, which were negatively correlated with CRP [10]. This highlights the difficulty in interpreting serum copper levels in the setting of inflammation.…”
Section: Trace Elementsmentioning
confidence: 99%
“…Levels can be low in hypoalbuminemia as it is bound to albumin and alpha-macroglobulins in the blood [31]. Zinc has been found to correlate negatively with CRP [10]. A review found that, in minor illness (CRP < 15 mg/L), zinc was decreased by 10%, whereas major illness (CRP 100–200 mg/L) caused a 40%–60% decrease [32].…”
Section: Trace Elementsmentioning
confidence: 99%
“…Biomarkers such as C‐reactive protein (CRP), interleukin 6, and ceruloplasmin were not consistently available for the patients in our cohort because all laboratory data measurements were traditionally entered individually by a member of the primary medical team. Therefore, we were unable to fully interpret observed micronutrient deficiencies in the context of acute inflammation 48 . Additionally, there was a shift from standard CRP assays to high‐sensitivity CRP (hs‐CRP) over the study period, thereby increasing the heterogeneity of available inflammatory markers for analysis.…”
Section: Discussionmentioning
confidence: 99%